2015
DOI: 10.1002/pc.23865
|View full text |Cite
|
Sign up to set email alerts
|

Segregated conductive network of MWCNT in PA12/PA6 composites: Electrical and rheological behavior

Abstract: In the present study, different quantities of multiwalled carbon nanotubes and an immiscible blend of polyamides, 50 vol%/50 vol%. Polyamide 12/polyamide 6 (PA12/PA6), are melt blending by extrusion to obtain conducting polymer composites. The rheological and electrical properties of nanocomposites are evaluated as function of nanofiller content. Both rheological and electrical percolation thresholds are calculated by graphical methods and fitting the experimental data to the well‐known power‐law expression. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 35 publications
3
25
0
Order By: Relevance
“…Laura Arboleda‐Clemente et al designed new CNT nanocomposites—with an immiscible blend of polyamides as a matrix—that had good electrical conductivity and a low percolation threshold. They used rheological tests and alternating current (AC) measurements to determine the percolation threshold of nanocomposites.…”
Section: Polyamide Nanocomposites Based On Carbon Nanofillersmentioning
confidence: 99%
“…Laura Arboleda‐Clemente et al designed new CNT nanocomposites—with an immiscible blend of polyamides as a matrix—that had good electrical conductivity and a low percolation threshold. They used rheological tests and alternating current (AC) measurements to determine the percolation threshold of nanocomposites.…”
Section: Polyamide Nanocomposites Based On Carbon Nanofillersmentioning
confidence: 99%
“…From electrical and rheological measurements, a low percolation threshold was determined, probably due to the high aspect ratio of the nanotubes which is kept after the composite processing, and to the preferential localization of CNTs in the polyamides interfaces (the latter was confirmed by transmission electron microscopy [TEM]). 17 Other authors found an improvement in electrical behavior using conductive polymer composites with segregated networks. 18 The water uptake at saturation of nanocomposites decreases with respect to the pristine PA6 because of the diffusion of water molecules into the polymer matrix was slower.…”
Section: Introductionmentioning
confidence: 98%
“…The brittleness was indicated by SEM images of the tensile fracture surfaces, as shown in Figure 9(a–d). The tensile modulus of the PP/carbon composites increased with the carbon content owing to the PP/carbon network formation, which restricted the movement of the PP chains 56 . Although the addition of carbon increases the tensile properties with low concentrations, at high carbon loading, the tensile strength has reduced.…”
Section: Resultsmentioning
confidence: 99%